Utilization of GIS Techniques as Decision Support System for Location of Filling Stations in Minna, Niger State, Nigeria - J Yisa; Oluwaseun Olubadewo-Joshua; Oboh Satur Okosun (Geosfera Indonesia, 2019)
The study demonstrated that spatial analysis with relevant socio-economic sources and physical parameter from different sources can be evaluated for the filling station sites planning. This has demonstrated the importance of Geographic Information System (GIS) application in predicting and determining of site criteria for filling stations facilities development, most especially in areas where there is land uses competition which requires consumer accessibility, sustainability, environmental safety, environmentally sensitive development solutions, etc. A stratified sampling technique was used to select the sample size and administration of the questionnaire. The data collected was analyzed using descriptive statistics such as frequency distribution, bar chart, pie chart and percentage and maps showing the sampled existing filling stations in the study area. The result shows the distribution of filling stations located across the study area. This study shows that GIS and multi-criteria analysis are essential tools to assist in correct siting to national planners and decision-makers in deciding the most appropriate filling stations location pattern to apply in Minna and its environs. Keywords: GIS, filling stations, spatial distribution, location, distance. References Aklilu, A., & Necha, T. (2018). Analysis of the spatial accessibility of addis Ababa’s light rail transit: The case of East–West corridor. Urban Rail Transit, 4(1), 35-48. doi:10.1007/s40864-018-0076-6 Dhiman, R., Kalbar, P., & Inamdar, A. B. (2019). Spatial planning of coastal urban areas in india: Current practice versus quantitative approach. Ocean and Coastal Management, 182 doi:10.1016/j.ocecoaman.2019.104929 Tah, D.S (2017). GIS-based locational analysis of Petrol filling stations in Kaduna metropolis: Science World Journal, Vol 12(2): 8-12. Emakoji, M.A., and Otah K.N (2018). Managing Filling Stations Spatial Database using an innovative GIS tool- a case study of Afipko City in Nigeria: Asian Journal of Geographical Research, 1(2):1-9, 2018 Jahangiri, M., Ghaderi, R., Haghani, A., & Nematollahi, O. (2016). Finding the best locations for establishment of solar-wind power stations in middle-east using GIS: A review. Renewable and Sustainable Energy Reviews, 66, 38-52. doi:10.1016/j.rser.2016.07.069 Jelokhani-Niaraki, M., Hajiloo, F., & Samany, N. N. (2019). A web-based public participation GIS for assessing the age-friendliness of cities: A case study in tehran, iran. Cities, 95 doi:10.1016/j.cities.2019.102471 Loidl, M., Witzmann-Müller, U., & Zagel, B. (2019). A spatial framework for planning station-based bike sharing systems. European Transport Research Review, 11(1) doi:10.1186/s12544-019-0347-7 Ma, Y., & Gopal, S. (2018). Geographicallyweighted regression models in estimating median home prices in towns of massachusetts based on an urban sustainability framework. Sustainability (Switzerland), 10(4) doi:10.3390/su10041026 Maanan, M., Maanan, M., Rueff, H., Adouk, N., Zourarah, B., & Rhinane, H. (2018). Assess the human and environmental vulnerability for coastal hazard by using a multi-criteria decision analysis. Human and Ecological Risk Assessment, 24(6), 1642-1658. doi:10.1080/10807039.2017.1421452 Khahro, S. H., Matori, A. N., Chandio, I. A., & Talpur, M. A. H. (2014). Land Suitability Analysis for Installing New Petrol Filling Stations Using GIS. Procedia Engineering, 77, 28–36. doi:10.1016/j.proeng.2014.07.024 Mustapha, O.O (2016). Assessment of filling stations in Illorin, Kwara State, Nigeria using Geospatial technologies, IJSRCSEIT vol 1(2) 69-73, 2016 Naboureh, A., Feizizadeh, B., Naboureh, A., Bian, J., Blaschke, T., Ghorbanzadeh, O., & Moharrami, M. (2019). Traffic accident spatial simulation modeling for planning of road emergency services. ISPRS International Journal of Geo-Information, 8(9) doi:10.3390/ijgi8090371 Peprah (2018). Suitability analysis of siting oil and gas filling station using multi-criteria decision analysis and GIS approach- a case study of Tarkwa and environs- Ghana: Journal of Geomatics, vol 12(2): 158-166, 2018 Sacramento Gutierres, F., Torrente, A. O., & Torrent-Moreno, M. (2019). Responsive geographical information systems for spatio-temporal analysis of mobile networks in barcelona. Architecture, City and Environment, 14(40), 163-192. doi:10.5821/ace.14.40.5349 Vaz, E., Lee, K., Moonilal, V., & Pereira, K. (2018). Potential of geographic information systems for refugee crisis: Syrian refugee relocation in urban habitats. Habitat International, 72, 39-47. doi:10.1016/j.habitatint.2017.02.001 Copyright (c) 2019 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License